2008
DOI: 10.1111/j.1742-4658.2008.06503.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of ZP1 into perivitelline membrane after in vivo treatment with exogenous ZP1 in Japanese quail (Coturnix japonica)

Abstract: The avian vitelline membrane in laid eggs consists of three layers: the outer layer; the continuous membrane; and the inner layer [1]. The outer layer, which is composed of a varying number of sublayers of latticed fine fibrils, is formed in the infundibulum part of the oviduct [2]. The continuous membrane, which is a very thin granular membrane, is also formed in the infundibulum [2]. The inner layer, a 3D network of coarse fibers, is found between the granulosa cells and the oocyte in follicles before ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Additionally, we found that ZP1, which circulates in the bloodstream, received some modifications during transport to the pvm. It is from the fact that when ZP1 purified from the serum of laying quail was injected into different birds, the signal of exogenous ZP1 was detected in the pvm, whereas ZP1 derived from the pvm failed to incorporate into the pvm (Kinoshita et al 2008). In this report, we demonstrate for the first time that the ubiquitin-proteasome system functions in avian fertilization.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, we found that ZP1, which circulates in the bloodstream, received some modifications during transport to the pvm. It is from the fact that when ZP1 purified from the serum of laying quail was injected into different birds, the signal of exogenous ZP1 was detected in the pvm, whereas ZP1 derived from the pvm failed to incorporate into the pvm (Kinoshita et al 2008). In this report, we demonstrate for the first time that the ubiquitin-proteasome system functions in avian fertilization.…”
Section: Introductionmentioning
confidence: 68%
“…To prepare the affinity gel for the separation of serum ZP1, the IgG fractionated from anti-ZP1 antiserum (Kinoshita et al 2008) with a HiTrap Protein A FF affinity column (Amersham Pharmacia Biotech) that had been covalently coupled to NHS-activated sepharose (Amersham Pharmacia Biotech) according to the manufacturer's instructions. The serum of laying birds was incubated with the affinity gel for 16 h at 4 8C.…”
Section: Purification Of Serum and Pvm Zp1mentioning
confidence: 99%
“…As was mentioned earlier, the PL in quail as well as in chicken is constructed mainly by ZP1 and ZP3, and these components specifically bind to form the PL fiber , Sasanami et al 2006, Okumura et al 2007a, 2007b, Kinoshita et al 2008. In fact, in vitro incubation of ZP1 with ZP3 spontaneously produced fibrous aggregates, which were visible under optical microscopy (Okumura et al 2007b).…”
Section: Discussionmentioning
confidence: 93%
“…We found that ZP1, which circulates in the bloodstream, received some modifications during transport to the pvm. It is from the fact that when ZP1, purified from the serum of laying quail, was intravenously injected into different birds, the signal of exogenous ZP1 was detected in the pvm, whereas ZP1 derived from the pvm failed to incorporate into the pvm (Kinoshita et al, 2008). As described above, egg envelope glycoprotein ZP1 is the authentic AR inducer in birds.…”
Section: Protease Responsible For Pvm Digestionmentioning
confidence: 99%